Reputational concerns in the market for corporate control - Boone, Audra; Uysal, Vahap B. (Journal of Corporate Finance, 2020)
This paper explores whether corporate acquirers consider environmental reputations when planning and structuring takeovers. We find that firms with an environmentally toxic reputation, which have the greatest potential for negative spillovers to their merger partners, have a lower associated probability of being both acquirers and targets. Acquirers are more likely to pair with similar reputation firms and are less likely to acquire firms with lower reputations. Most notably, green firms in our sample never acquire toxic firms. Acquirers that buy firms with differing environmental reputations use a higher percentage of stock in their acquisition offers. We further show that the returns to acquirers are lower when they acquire firms outside of their area. Collectively, these findings suggest that managers account for potential negative spillover effects in acquisition decisions.